High-Level Adaptation and Aftereffects - Stefania D'Ascenzo (Frontiers Research Topics, 2017)
Aftereffects generally occur after a prolonged exposure (adaptation) to a first stimulus possessing one given property followed by presentation of a stimulus bearing a neutral value of that property. The aftereffect consists in a change in appearance of the neutral stimulus following the adapter, compared to the appearance of the neutral stimulus when it is perceived without any previous exposure to the adapter. The transient phenomena of perceptual aftereffects are believed to depend on the activation of neuron populations that respond selectively to a given property of the stimuli. Studying how adaptation occurs (which stimulus properties are sensitive to it, which timings are necessary, whether individual differences modulate its occurrence) has thus become an indirect way to probe the plasticity of sensory functions in the nervous system, recently extending to more cognitive and representational aspects of neural coding. In the last two decades, indeed, it has been demonstrated that aftereffects occur not only for low-level properties of stimuli (such as motion, color, or orientation) but also for high-level properties. Many studies have proven that high-level proprieties of the stimuli, e.g. gender, identity, ethnicity, or age of a face or a voice, are sensitive to this phenomenon. It has been shown, for example, that the prolonged exposure to a female or male face produces a gender misperception in the opposite direction when an androgynous face is shown after the adapter. Furthermore, recent studies have also shown that aftereffects are not strictly contingent upon the physical features that make up stimuli, but they seem to run across the high-level proprieties subjects are adapted to. These evidences are supported by cross-category adaptation studies, which underlie how aftereffects occur even across stimuli that do not share physical features (e.g. bodies and faces) but that instead, share common higher-level properties, such as gender. Given the growing body of research focused on adaptation and aftereffects in high-level perception at the boundaries with perceptual learning, attention and cognition, the purpose of this topic is to provide a picture of the state of the art relative to the specific phenomena of adaptation in high-level perceptual processing.